2023
DOI: 10.1002/jcv2.12185
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between elimination disorders and internalizing‐externalizing problems in children: A systematic review and meta‐analysis

Abstract: BackgroundElimination disorders are highly prevalent in childhood and often associated with clinically relevant comorbid psychological disorders. The aim of this study is to determine if, and to what extent, children with elimination disorders show higher internalizing and externalizing problems than their healthy peers.MethodsA multistep literature search was performed from database inception until May 1st, 2022. PRISMA/MOOSE‐compliant systematic review (PROSPERO: CRD42022303555) were used to identify studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…An important focus of the studies in the special issue is on outcomes and prognosis, such as those demonstrating an association between Attention-Deficit/Hyperactivity Disorder (ADHD) and cardiovascular problems (Li et al, 2023) and sleep problems (Marten et al, 2023), as well as for poor health-related quality of life associated with low socio-economic status amongst children and adolescents with ADHD (Sevastidis et al, 2023). Bogdan et al (2023) presented a comprehensive summary of the main characteristics of longitudinal studies investigating child and adolescent mental health conditions in the general population; Aymerich et al (2023) found that internalising and externalising problems are present in children with enuresis or encopresis; while Pollard et al (2023) observed that anxiety problems during childhood are associated with multifaceted poor outcomes and considerable economic costs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An important focus of the studies in the special issue is on outcomes and prognosis, such as those demonstrating an association between Attention-Deficit/Hyperactivity Disorder (ADHD) and cardiovascular problems (Li et al, 2023) and sleep problems (Marten et al, 2023), as well as for poor health-related quality of life associated with low socio-economic status amongst children and adolescents with ADHD (Sevastidis et al, 2023). Bogdan et al (2023) presented a comprehensive summary of the main characteristics of longitudinal studies investigating child and adolescent mental health conditions in the general population; Aymerich et al (2023) found that internalising and externalising problems are present in children with enuresis or encopresis; while Pollard et al (2023) observed that anxiety problems during childhood are associated with multifaceted poor outcomes and considerable economic costs.…”
mentioning
confidence: 99%
“…( 2023 ) presented a comprehensive summary of the main characteristics of longitudinal studies investigating child and adolescent mental health conditions in the general population; Aymerich et al. ( 2023 ) found that internalising and externalising problems are present in children with enuresis or encopresis; while Pollard et al. ( 2023 ) observed that anxiety problems during childhood are associated with multifaceted poor outcomes and considerable economic costs.…”
mentioning
confidence: 99%